Cultural domination : philosophical perspectives - Besch, Thomas M., 1966-; Kincaid, Harold, 1952-; Menon, Tarun; Riel, Raphael van, 1979- (New York, NY : Routledge, 2025)
"Cultural domination has received attention inside and outside of academia, but it remains under-explored in recent philosophical debate. To fill this gap, this book brings together ten original research contributions that engage the theme from a variety of different perspectives. They range from contributions to the philosophy of social science to advanced work in normative political philosophy. The diversity of approaches reflects the intellectual richness of the theme. Ideas of cultural domination not only raise complex conceptual and methodological questions that can challenge our understandings of domination or culture; such ideas can also play an important role both in explanations of salient social phenomena, such as social structures, and in an evaluation and critique of such phenomena. The diversity of styles of analysis, theoretical commitments, and normative frameworks across the chapters makes this book ideal for advanced undergraduate and graduate students looking for an entry point into this complex issue, as well as for scholars in philosophy, social science, and cultural studies interested in the current state of the art"--
Keywords: Culture -- Philosophy